Childhood Maltreatment and Adolescent Cyberbullying Perpetration: A Moderated Mediation Model of Callous—Unemotional Traits and Perceived Social Support. Issue 7 (April 2022) - Fang, Jie; Wang, Wei; Gao, Ling; Yang, Jiping; Wang, Xingchao; Wang, Pengcheng; Wen, Zhonglin
Although childhood maltreatment has been shown to play an important role in adolescent cyberbullying perpetration, little is known about mediating and moderating mechanisms underlying this relationship. The current study investigated the mediating role of callous-unemotional (CU) traits in the association between childhood maltreatment and adolescent cyberbullying perpetration, as well as the moderating role of perceived social support. A total of 2, 407 Chinese adolescents (aged 11–16 years, Mage = 12.75 years, SD = 0.58) completed the measures of childhood maltreatment, CU traits, cyberbullying perpetration, and perceived social support. The results showed that CU traits partially mediated the relationship between childhood maltreatment and adolescent cyberbullying perpetration. Furthermore, perceived social support moderated the relationship between childhood maltreatment and CU traits, as well as CU traits and cyberbullying perpetration. Specifically, childhood maltreatment had a greater impact on CU traits for adolescents with higher levels of perceived social support and the predictive function of CU traits on cyberbullying perpetration was stronger for adolescents with low levels of perceived social support.